Effectiveness of English Medium Instruction Implementation on Boarding Maritime Education - Kasan Gupron, Akhmad; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
The implementation of EMI in boarding maritime education can help cadets prepare for an increasingly connected global maritime work environment. The application of EMI can help improve cadets' English skills and expand their learning opportunities in accessing the international curriculum. In an increasingly complex global maritime environment requiring good English skills, the use of EMI can help cadets to be ready for future challenges. However, challenges such as increased costs and skilled human resources in teaching in English and providing language support for cadets also need to be addressed in the implementation of EMI in boarder maritime education